(untitled) (Al-Farooq Journal of Sciences, 2026)
This research addresses contemporary visual arts in the context of digital transformation through analytical approach that explores the dialectical relationship between technology and aesthetics. It aims to examine how digital media and modern technologies have influenced the structure of the artwork in terms of both form and content as well as the nature of audience reception and interaction. The study highlights the shifts in aesthetic concepts resulting from. The integration of art and technology, leading the emergence of new artistic forms such as digital art and interactive art it also relies on the analysis of selected contemporary art works to demonstrate the dimensions of this dialectic, emphasizing the role of the audience as an active participant in meaning making within the digital artistic experience.